2008
DOI: 10.1172/jci33187
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte analysis from WHIM syndrome patients reveals a pivotal role for GRK3 in CXCR4 signaling

Abstract: Leukocytes from individuals with warts, hypogammaglobulinemia, infections, and myelokathexis (WHIM) syndrome, a rare immunodeficiency, and bearing a wild-type CXCR4 ORF (WHIM WT ) display impaired CXCR4 internalization and desensitization upon exposure to CXCL12. The resulting enhanced CXCR4-dependent responses, including chemotaxis, probably impair leukocyte trafficking and account for the immunohematologic clinical manifestations of WHIM syndrome. We provided here evidence that GPCR kinase-3 (GRK3) specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
137
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 105 publications
(146 citation statements)
references
References 48 publications
(56 reference statements)
5
137
1
3
Order By: Relevance
“…30 The WHIM syndrome (wart, hypogammaglobulinemia, infection, and myelokathexis syndrome), which is a syndrome characterized by disseminated HPVinduced warts, leukopenia due to bone marrow cell retention and other immune dysfunctions, has been correlated to a defect in CXCR4 receptor and CXCL12 signal transmission, thus confirming a major role of the cytokine in contributing to immune cell dysregulation and T cell-impaired trafficking in the context of HPVderived lesions. 31 Our study confirmed a significant relationship between HPV typing and CXCL12% area in both squamous and glandular neoplastic lesions, showing an increase of CXCL12% area in cases that were positive for both HPV6,11 and HPV16ϩ probes compared with cases that were negative for both probes. Interestingly, cases that were positive for only HPV6,11 demonstrated a higher CXCL12% area than those that were only HPV16ϩ positive.…”
Section: Cxcl12 and Foxp3supporting
confidence: 84%
“…30 The WHIM syndrome (wart, hypogammaglobulinemia, infection, and myelokathexis syndrome), which is a syndrome characterized by disseminated HPVinduced warts, leukopenia due to bone marrow cell retention and other immune dysfunctions, has been correlated to a defect in CXCR4 receptor and CXCL12 signal transmission, thus confirming a major role of the cytokine in contributing to immune cell dysregulation and T cell-impaired trafficking in the context of HPVderived lesions. 31 Our study confirmed a significant relationship between HPV typing and CXCL12% area in both squamous and glandular neoplastic lesions, showing an increase of CXCL12% area in cases that were positive for both HPV6,11 and HPV16ϩ probes compared with cases that were negative for both probes. Interestingly, cases that were positive for only HPV6,11 demonstrated a higher CXCL12% area than those that were only HPV16ϩ positive.…”
Section: Cxcl12 and Foxp3supporting
confidence: 84%
“…Phenotypic results were expressed as the relative mean fluorescence intensity (MFI), corresponding to the MFI of the specific label/MFI of the isotype control. CCR5, CCR7, and CXCR4 expression was analyzed with a LSR-Fortessa cytometer, and the results were displayed in MFI, as previously described (48). Cell viability was determined by labeling with annexin V and 7-aminoactinomycin D, following the manufacturer's instructions, followed by analysis on a FACSCalibur cytometer.…”
Section: Net Pretreatment and Modc Activationmentioning
confidence: 99%
“…Binding of CXCL12 to CXCR4 causes ligand-dependent conformational changes in the receptor, resulting in phosphorylation of the intracellular C-terminus of CXCR4 by protein kinase C and G protein-coupled receptor kinases (GRK) such as GRK3. 17 The phosphorylated receptor then recruits a member of the β-arrestin family of cytosolic scaffolding proteins, either β-arrestin-1 or β-arrestin-2. The interaction between activated chemokine receptor and β-arrestin causes internalization of the bound chemokine-receptor pair and regulates signaling through downstream effector molecules such as ERK1/2.…”
mentioning
confidence: 99%